Thermogravimetric Analysis of Poly-N-(4-vinylphenyl)alkyl Dithiocarbamates - MEGHEZZI, AHMED; DADAMOUSSA, BELKHIR; LAKHDAR, YOUCEF (Asian Journal of Chemistry, 2010)
Poly-N (4-vinylphenyl)alkyl dithiocarbamates was prepared by radical polymerization. The chemical structures of the polymers were characterized by FT-IR spectroscopy and elemental analysis. The physical properties of polymers including solution viscosity, thermal stability and thermal behaviour were studied as well. The polymer showed an excellent stability. Their inherent viscosities were in the range of 0.7-1.0 dL/g. Thermal study of the poly-N-(4-vinylphenyl)- alkyl dithiocarbamates and their copolymers with styrene and isothiocyanatostyrene shows an elimination of alkyl mercaptans at the first stage but at the second stage we observe a reticulation of chains of the macromolecules during the thermolysis process. We observe also that the temperature of the total destruction of the poly-N-(4-vinylphenyl)alkyl dithiocarbamates and copolymers increases about 250 ºC comparatively to the polystyrene.